2011
DOI: 10.1523/jneurosci.1691-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Analysis Does Not Occur in the Absence of Awareness Induced by Interocular Suppression

Abstract: It has been intensely debated whether visual stimuli are processed to the point of semantic analysis in the absence of awareness. In the present study, we measured the extent to which the meaning of a stimulus was registered using the N400 component of human event-related potentials (ERPs), a highly sensitive index of the semantic mismatch between a stimulus and the context in which it is presented. Observers judged the semantic relatedness of a context and target word while ERPs were recorded under continuous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
85
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 75 publications
(103 reference statements)
6
85
1
Order By: Relevance
“…For example, they contrast with an older literature on binocular rivalry which had concluded that high-level conceptual or semantic processing was diminished for suppressed stimuli (Zimba & Blake, 1983). More recently, using CFS, Kang, Blake and Woodman (2011) found no evidence that the meanings of individual words were accessed when they were suppressed (although see Heyman and Moors, 2012, for a critique of that procedure), while Yang and Yeh (2011) found that emotionally negative Chinese words were in fact slower to break suppression than neutral words, a finding in the opposite direction to the effect found by Sklar and colleagues. 1 Recent work on statistical inference and measurement has emphasized that such inconsistent results might be expected when experiments with low statistical power are used to test for small or null effects (Gelman & Carlin, 2014), and these worries are particularly marked in this instance given concerns that data from the b-CFS method are potentially very noisy (e.g., breaking times often have a very long right tail, Moors, Stein, Wagemans, & van Ee, 2015;Stein, Hebart, & Sterzer, 2011).…”
mentioning
confidence: 66%
“…For example, they contrast with an older literature on binocular rivalry which had concluded that high-level conceptual or semantic processing was diminished for suppressed stimuli (Zimba & Blake, 1983). More recently, using CFS, Kang, Blake and Woodman (2011) found no evidence that the meanings of individual words were accessed when they were suppressed (although see Heyman and Moors, 2012, for a critique of that procedure), while Yang and Yeh (2011) found that emotionally negative Chinese words were in fact slower to break suppression than neutral words, a finding in the opposite direction to the effect found by Sklar and colleagues. 1 Recent work on statistical inference and measurement has emphasized that such inconsistent results might be expected when experiments with low statistical power are used to test for small or null effects (Gelman & Carlin, 2014), and these worries are particularly marked in this instance given concerns that data from the b-CFS method are potentially very noisy (e.g., breaking times often have a very long right tail, Moors, Stein, Wagemans, & van Ee, 2015;Stein, Hebart, & Sterzer, 2011).…”
mentioning
confidence: 66%
“…This alternative depends on the suppressed image receiving substantial semantic processing. However, existing evidence suggests that CFS (and interocular suppression more broadly) seems to interfere with visual processes occurring before semantic analysis of words (48,49) and objects (50,51); for example, interocularly suppressed words and objects cannot prime subsequent processing of related stimuli (52), and neurons in medial temporal cortex do not respond to images suppressed through CFS in humans (53) or suppressed through binocular rivalry in monkeys (54). *This hit rate is substantially higher than the 50% QUEST threshold to which the staircasing procedure was set because participants' performance tends to improve during the course of the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…A possible reason for these discrepancies may be due to restricted visual inputs that are frequently used to study visual awareness rather than the necessity of awareness for higher level processing per se. In one illuminating example, when awareness was manipulated with visual masking (Breitmeyer, 1984), unconscious semantic processing occurred (Naccache & Dehaene, 2001; Van den Bussche, Notebaert, & Reynvoet, 2009); however, when awareness was manipulated with continuous flash suppression (CFS, Tsuchiya & Koch, 2005), unconscious semantic processing was absent (Kang, Blake, & Woodman, 2011). …”
mentioning
confidence: 99%